The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.9734/indj/2019/v13i3-430114
|View full text |Cite
|
Sign up to set email alerts
|

Psychoactive Substance and Psychopathological Symptoms among Nigerian Secondary Schools Adolescents

Abstract: Aim: Abuse of psychoactive substances among secondary school adolescents is a huge problem globally. This study examined the influence of psychoactive substance use on psychopathological symptoms among secondary school adolescents in Ede, Osun State, Southwestern Nigeria. Study Design: Cross-sectional survey design.              Place of Study: Redeemer’s University Ede Osun state, Southwestern Nigeria. Methodology: Four hundred and ninety-six (496) secondary school adolescents (mean age 15.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
1
3
0
Order By: Relevance
“…The study further uncovered that most people take OTC drugs when they are ill. This observation aligns with Akinnawo, Onisile, Alakija, and Akpunne [21] whose study reported the prevalent use of OTC drugs in Southwest Nigeria. The study found that antimalarial drugs are the most consumed OTC drugs in Awka South LGA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The study further uncovered that most people take OTC drugs when they are ill. This observation aligns with Akinnawo, Onisile, Alakija, and Akpunne [21] whose study reported the prevalent use of OTC drugs in Southwest Nigeria. The study found that antimalarial drugs are the most consumed OTC drugs in Awka South LGA.…”
Section: Discussionsupporting
confidence: 90%
“…This finding aligns with the outcome of a study by Akinnawo et.al. [21] which reported that OTC drugs are considered to be highly effective. The study also discovered that many people usually recommend OTC drugs to their family members, relatives, friends, and their wider social cycle.…”
Section: Discussionmentioning
confidence: 99%
“…This escalation can worsen the psychological impact and create a cycle of dependence. It is important to note that the relationship with substance use on psychological well-being can vary widely depending on individual factors, the type and frequency of substance use, and the presence of underlying psychological well-being issues [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the wrong perception of the illness severity, belief in self-care, non-availability of physicians, and previous pleasant experiences with SM are among the identified causes of SM in most societies (18)(19)(20). Research findings report a high prevalence of SM with OTC and prescription drugs among the Nigerian population (21)(22)(23)(24)(25), often resulting in psychological distresses ( 26) such as abnormal illness behavior.…”
Section: Introductionmentioning
confidence: 99%